From identity and image to intention: Mediating role of the experience economy in Shandong’s heritage tourism - Lijun, Dong; Yahaya, Mohd Fahmi (Edelweiss Applied Science and Technology, 2025)
This study investigates how cultural identity and destination image influence behavioral intention in the context of cultural heritage tourism in Shandong Province, China, applying the Stimulus–Organism–Response (SOR) model. Drawing on Pine and Gilmore’s Experience Economy framework, the research positions the four experiential realms (entertainment, education, aesthetics, and escapism) as mediators that transform cultural and perceptual cues into behavioral outcomes. Data were collected through a structured survey of 387 heritage tourists in Shandong and analyzed using structural equation modeling with bootstrapping procedures. The results indicate that both cultural identity and destination image exert significant positive effects on behavioral intention, and that these effects are partly mediated by the Experience Economy dimensions. The findings clarify contradictory results in previous studies where identity and image did not consistently predict intention, showing that experiential processes are the critical mechanism linking cultural cues with tourist behavior. The study makes three contributions: it extends the SOR model by explicitly testing the Experience Economy as a mediating construct, it enriches the understanding of cultural identity and destination image in heritage tourism, and it provides practical guidance for heritage managers in Shandong. Specifically, heritage experiences that combine identity cues with immersive, aesthetically appealing, and educational elements are most likely to foster loyalty and advocacy.